Ferroelectric Liquid Crystal Compound Lens Based on Pancharatnam–Berry Phase - Ying Ma; Mingkui Yin; Yuhang Shan; Vladimir G. Chigrinov; Hoi-Sing Kwok; Jianlin Zhao (Crystals, 2022)
We report a ferroelectric liquid crystal (FLC) compound lens based on the Pancharatnam–Berry (PB) phase. The phase of the FLC compound lens is an integration of polarization grating and a PB lens. Thus, when light passes through an FLC compound lens, the output light’s polarization handedness will be changed accordingly. In this case, FLC compound lenses can function as concave/convex lenses with spatially separated output light and rapid transmittance tunability. The FLC compound lenses were fabricated using a single-step holographic exposure system, based on a spatial light modulator working as numerous phase retarders. Photosensitive azo-dye material was used as the aligning layer. The output light transmittance of the FLC compound lens can be operated at 150 μs. Our results achieve the potential applications on various displays and augmented reality.